El consumo de pescado en la Amazonia Brasileña - Isaac, V. J.; Almeida, M.C. de (ISBN 978-92-5-307029-9 : Roma (Italia))
(Es)
Keywords: PESCADO; CONSUMO; ALIMENTOS; COMUNIDADES RURALES; BRASIL; AMAZONIA